Remembering and forgetting: directed forgetting effect in obsessive-compulsive disorder - Konishi, Mika (Dove Medical Press, 2011)
It has been reported that episodic memory seems to be impaired in patients with obsessive-compulsive disorder (OCD) because the patients repeat a specific checking behavior, but it is still unknown if OCD patients show memory impairments associated with their unique symptoms or not. To study episodic memory in OCD patients, we examined the directed forgetting effect. Patients with OCD and healthy control participants were given a list of 24 emotionally neutral everyday words (12 remember [R]-cued words and 12 forget [F]-cued words) under two conditions: List and Item. The results of our study showed that OCD patients recalled a number of F-cued words similar to that for controls and relatively fewer R-cued words than controls under both List and Item conditions. Consequently, the directed forgetting effect was smaller in OCD patients than controls. Our results demonstrated that both selective encoding and retrieval inhibition processes are impaired in OCD, and we suggest that recall of unfavorable items to be forgotten intruded into necessary items to be remembered. This impairment in episodic memory may partially account for some of the unique clinical symptoms of OCD.